Advances in mucin mimic synthesis and applications in surface science - Navarro, Luis A.; French, Daniel L.; Zauscher, Stefan (Current opinion in colloid & interface science, 2018)
Mucins are a class of glycoproteins that serve key roles in tissue protection, hydration, and lubrication. However, their study and application are complicated by their post-translational modifications, heterogeneity, and their propensity to deteriorate upon isolation. As a result, several groups have made strides in synthesizing mucin-mimicking compounds for systematic study and therapeutic applications. In this paper, we review general mucin structure, recent trends in the design and synthesis of mucin mimics, and the ways mucin analogues can outperform native mucins. Specifically, we highlight the structures of lubricin and aggrecan, which are the subject of many biomimetic approaches. Furthermore, we showcase the structural features that allow analogues to mimic mucin functions and categorize them based on their roles as monolayer coatings, gel formers, or adhesion promoters. Lastly, we examine the chemical composition of mucin analogues, emphasizing how modular approaches provide flexibility to repurpose mucin mimics for different applications. [Display omitted] •Mucins are a class of heavily glycosylated glycoproteins.•Mucin use is inhibited by batch heterogeneity, motivating synthesis of mucin mimics.•Mucin mimics can be categorized into motifs by the mucin role they intend to mimic.•In mimics, biological components confer specificity, and synthetic polymers offer structural control.•Modular mimics allow rapid repurposing for different applications and studies.